2009
DOI: 10.1111/j.1540-8191.2008.00759.x
|View full text |Cite
|
Sign up to set email alerts
|

Staged Surgical Palliation in Hypoplastic Left Heart Syndrome and Its Variants

Abstract: This report identified an outcome improvement after staged palliation of HLHS, attributed to an increase in experience and expertise gained over time. Lower operative weight, ascending aortic size, prolonged duration of cardiopulmonary bypass, and hypothermic circulatory arrest were identified to significantly influence early mortality after the Norwood procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 42 publications
(98 reference statements)
0
9
0
Order By: Relevance
“…While outcomes of staged reconstruction in the present era have become truly spectacular in experienced centers, still a few infants and children fail to respond satisfactorily [16]. Transplantation has occasionally become necessary, and this has occurred after each stage.…”
Section: Clinical Issues In Infant Heart Transplantationmentioning
confidence: 99%
“…While outcomes of staged reconstruction in the present era have become truly spectacular in experienced centers, still a few infants and children fail to respond satisfactorily [16]. Transplantation has occasionally become necessary, and this has occurred after each stage.…”
Section: Clinical Issues In Infant Heart Transplantationmentioning
confidence: 99%
“…Staged univentricular palliation, with the right ventricle serving as the systemic pumping chamber, has transformed HLHS from a lethal condition to a survivable one. 1-3 However, perioperative mortality and long-term morbidity remain significant challenges. 4-7 …”
Section: Introductionmentioning
confidence: 99%
“…32, 33 Many other recent studies of the outcomes after S2P have not found the timing of S2P to be associated with outcomes. 14, 16, 34, 35 Notably, risk factors for death or heart transplantation after S2P have not yet been reported in SVR Trial study participants. Schwartz, et al instead reported risk factors for prolonged hospital length of stay after S2P.…”
Section: Discussionmentioning
confidence: 99%